Functional adrenal oncocytoma: A rare neoplasm - Sharma Nitin; Dogra Prem; Mathur Sandeep (Wolters Kluwer Medknow Publications, 2008)
Adrenal oncocytoma is a rare adrenal neoplasm with only 21 cases reported in English literature. These adrenal tumors are usually nonfunctional and hence incidentally detected. Most of these adrenal neoplasms are benign. We report a rare case of adrenal oncocytoma that was functional and was successfully managed by laparoscopic adrenalectomy.